Volleyball players' somatic composition in the Final Six of 2019 FIVB Volleyball Nations League - Sieron, A.; Kolodynska, G. (Journal of Education, Health and Sport, 2019)
Introduction: International volleyball games are very popular. One of the youngest events in this discipline is the Volleyball Nations League, created by FIVB. It is important for trainers and researchers in which direction the best teams in the world are developing. Monitoring morpho-functional changes allows you to track potential trends in volleyball. Purpose: The aim of the study was to analyze sports results and the somatic composition of the best six teams participating in the 2019 FIVB Volleyball Nations League in Chicago. Material and methods: Research material involved volleyball players participating in the FIVB Volleyball Nations League (n = 73). Their age, height, weight, spike reach, block reach, and Rohrer`s index were analyzed. The mean value of the features and their derivatives in individual teams and groups were calculated and verified using statistical tests (t-Student, Kolmogorov-Smirniv`s) if the differences were significant. Results: The subjects` mean age was 26,73 years (SD = 3,73), mean body height was 200,25 cm (SD = 5,94), mean body weight was 89,70 kg (SD = 8,05), mean spike reach was 346,47 cm (SD = 10,87), mean block reach was 326,14 cm (SD = 12,66), mean Rohrer`s index was 1,12 (SD = 0,10). 94,52% of the volleyball players manifested the leptosomatic body composition, 5,48% the athletic one. The best team and the teams ranked 2-6 places in the analyzed tournament significantly differed in the block reach (P < 0,05). Conclusions: During the Final Six 2019 FIVB Volleyball Nations League in Chicago, the leptosomatic type of body was dominated by volleyballers at the highest level. The block reach significantly differentiate the winner of tournament and the others teams. These characteristics should be taken by trainers into account in team building to play men`s volleyball.